The effect of hormone replacement therapy on cervical cancer risk in perimenopausal women: a systematic review and meta-analysis of observational studies - Zhou, Yingna; Wei, Jie; Ruan, Youqin (Frontiers in Oncology, 2025)
BackgroundHormone replacement therapy (HRT) alleviates menopausal symptoms in perimenopausal women and help improve their quality of life, but its increased risk of cervical cancer (CC) remains to be evaluated.MethodsA system review and meta-analysis was conducted to retrieve literature related to HRT and CC risk by searching Pubmed, Embase, Science Direct, Web of Science, and Google Scholar databases. After screening the literature according to inclusion criteria and assessing the risk of bias using the Newcastle Ottawa Scale, the odd ratio (OR) values of HRT relative to CC were pooled.ResultsA total of 9 articles were included in this study, including 5 cohort studies and 4 case control studies. The sample size of perimenopausal women in the literature ranged from 60 to 584,742. The overall quality of the literature was good. The meta-analysis results showed that HRT (current and persist use) had a reduced risk for CC (OR=0.70, 95% confidence interval (CI) [0.58, 0.85]), an increased risk for any cytological abnormality related to CC (OR=1.38, 95% CI [1.22, 1.55]), also an increased risk for adenocarcinoma of CC (OR=1.82, 95% CI [0.91,3.65]), but a decreased risk for squamous cell carcinoma of CC (OR=0.74, 95% CI [0.57, 0.96]). The subtype was a significant source of heterogeneity in this meta-analysis.ConclusionHRT does not increase the overall risk of cervical cancer, but it increases the risk of cervical adenocarcinoma subtype and is associated with the risk of cancer-related cytological lesions.